Formulation and Evaluation of geranium oil Loaded carbon dots from the essential oil of pelargonium graveolens - Ahmed, Rafi; Pramodini, G.N.; Jatale, Ankita; Ansari, Imtiyaz; Mallalkar, Archana; Chopade, Swapnil; Mandale, Tejaswini; Iqra Naznin, Syed (Journal of Neonatal Surgery, 2025)
This research explores the development of carbon dots (CDs) loaded with geranium essential oil extracted from Pelargonium graveolens. The study involves the extraction of essential oil through hydro distillation, followed by characterization and preliminary analysis of the oil’s physical and chemical properties. The work emphasizes the potential of these bio-derived carbon dots for various applications, leveraging their unique optical and chemical stability, biocompatibility, and luminescent features. The comprehensive evaluation includes extraction yield, physicochemical constants, phytochemical screening, and preliminary formulation assessments. The findings suggest that geranium oil-loaded carbon dots exhibit promising properties for use in sensing, bioimaging, and other nanotechnology-based applications, highlighting their potential as sustainable and biocompatible nanomaterials.